2015
DOI: 10.1038/mtna.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency Generation of Multiple Short Noncoding RNA in B-cells and B-cell-derived Extracellular Vesicles

Abstract: Short noncoding (snc)RNAs are important new players in the landscape of biologics with therapeutic potential. Recently, we reported on a new method for the synthesis and delivery of snc RNA in B-cells transfected with plasmid DNA. Here using the same approach, we demonstrate that B-cells can be programmed for the enforced biogenesis and synchronous release of multiple sncRNAs. Our data show that this goal is feasible and that multiple sncRNA are released in the extracellular compartment in amounts comparable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…At the outset, we reasoned that restoring miR-335 content in LM2 cells would be best achieved by transfecting B cells with a plasmid engineered with two miR-335 precursor stem loops 15 . The general approach and the generation of iEVs in B cells by transfection with plasmid DNA are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the outset, we reasoned that restoring miR-335 content in LM2 cells would be best achieved by transfecting B cells with a plasmid engineered with two miR-335 precursor stem loops 15 . The general approach and the generation of iEVs in B cells by transfection with plasmid DNA are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that B cells can be reprogrammed for the enforced biogenesis and synchronous release of short noncoding (snc)RNAs 14 . sncRNAs were packaged and enriched as cargo in extracellular vesicles (EVs) induced in B cells (iEVs), with an estimate content of 3.6 copy number/iEV 15 . Here, we demonstrate that iEVs programmed to contain miR-335 cargo deliver and durably restore miR-335 to LM2 cells, modulate target mRNA expression in vitro and in vivo , and greatly reduce the growth of orthotopic LM2 tumors in immune deficient NSG mice.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes derived from Treg cells can suppress Th1 cell proliferation and cytokine production by transferring microRNA Let-7d to Th1 cells [120]. Furthermore, B-cell derived EVs can carry multiple short noncoding RNA molecules that may be involved in a variety of processes in immunity and inflammation [121]. In addition, B cell-derived exosomes express functional integrins that can mediate cell-cell adherence during inflammation [122].…”
Section: T-cell and B-cell Derived Extracellular Vesiclesmentioning
confidence: 99%
“…miRNAs are involved in the regulation of a variety of cellular processes, including cancer cell growth and metastasis [14][15][16][17] . Recently, this laboratory developed a novel technology wherein B lymphocytes can be programmed with suitable engineered plasmid DNA to enforce the release of extracellular vesicles (iEVs) with a predetermined miRNA payload [18,19] .…”
Section: Introductionmentioning
confidence: 99%